Small Molecules Functionalized Zinc Oxide Interlayers for High Performance Low‐Temperature Carbon‐Based CsPbI2Br Perovskite Solar Cells. Issue 7 (9th December 2022) - Zhang, Dan; Zhang, Xiang; Guo, Tonghui; Zou, Junjie; Zhou, Yuan; Jin, Junjun; Zhu, Zhenkun; Cao, Qiang; Zhang, Jing; Tai, Qidong
Abstract: The charge recombination resulting from bulk defects and interfacial energy level mismatch hinders the improvement of the power conversion efficiency (PCE) and stability of carbon‐based inorganic perovskite solar cells (C‐IPSCs). Herein, a series of small molecules including ethylenediaminetetraacetic acid (EDTA) and its derivatives (EDTA‐Na and EDTA‐K) are studied to functionalize the zinc oxide (ZnO) interlayers at the SnO2 /CsPbI2 Br buried interface to boost the photovoltaic performance of low‐temperature C‐IPSCs. This strategy can simultaneously passivate defects in ZnO and perovskite films, adjust interfacial energy level alignment, and release interfacial tensile stress, thereby improving interfacial contact, inhibiting ion migration, alleviating charge recombination, and promoting electron transport. As a result, a maximum PCE of 13.94% with a negligible hysteresis effect is obtained, which is one of the best results reported for low‐temperature CsPbI2 Br C‐IPSCs so far. Moreover, the optimized devices without encapsulation demonstrate greatly improved operational stability. Abstract : In this work, the zinc oxide films armored by ethylenediaminetetraacetic acid (EDTA) and its derivatives (EDTA‐Na and EDTA‐K) as the multifunctional interlayers are comprehensively explored to optimize SnO2 /CsPbI2 Br buried interface for low‐temperature carbon‐based inorganic perovskite solar cells. As a result, the optimized devices achieve the highest efficiency of 13.94%, along with enhanced moisture, thermal, and ultraviolet light stability.